2016
DOI: 10.1038/srep26600
|View full text |Cite
|
Sign up to set email alerts
|

The immiscibility of InAlN ternary alloy

Abstract: We have used two models based on the valence force field and the regular solution model to study the immiscibility of InAlN ternary alloy, and have got the spinodal and binodal curves of InAlN. Analyzing the spinodal decomposition curves, we obtain the appropriate concentration region for the epitaxial growth of the InN-AlN pseudobinary alloy. At a temperature most common for the epitaxial growth of InAlN (1000 K), the solubility of InN is about 10%. Then we introduce the mismatch strain item into the Gibbs fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 30 publications
2
11
0
4
Order By: Relevance
“…When the compressive strain is brought to 2%, T c increases abruptly to reach 3336 K. In contrast, applying a tensile stress of 2% still decreases the critical temperature T c that reaches 925 K. Therefore, whichever the direction of increase in strain (increase or decrease in indium concentration), below 1.5% for the growth of InAlN for instance on GaN, the unstable region is significantly reduced with a T c that can be as low as 586 K. This work is in agreement with the results reported in reference which studied the InAlN/GaN alloys and pointed out possible phase separation at indium rich composition ranges where the compressive strain is also highest. We also agree with the recent calculations of Zhao et al who reported that knowing the lattice mismatch may help in a search for the most adequate substrates for the InAlN alloy; most importantly, our results show that one should stay at small compressive strains.…”
Section: Phase Diagram Under Stress For Inaln Alloysupporting
confidence: 93%
“…When the compressive strain is brought to 2%, T c increases abruptly to reach 3336 K. In contrast, applying a tensile stress of 2% still decreases the critical temperature T c that reaches 925 K. Therefore, whichever the direction of increase in strain (increase or decrease in indium concentration), below 1.5% for the growth of InAlN for instance on GaN, the unstable region is significantly reduced with a T c that can be as low as 586 K. This work is in agreement with the results reported in reference which studied the InAlN/GaN alloys and pointed out possible phase separation at indium rich composition ranges where the compressive strain is also highest. We also agree with the recent calculations of Zhao et al who reported that knowing the lattice mismatch may help in a search for the most adequate substrates for the InAlN alloy; most importantly, our results show that one should stay at small compressive strains.…”
Section: Phase Diagram Under Stress For Inaln Alloysupporting
confidence: 93%
“…However, the current growth techniques (e.g. reactive dc magnetron co-sputtering) [24][25][26] rely on non-equilibrium processes to overcome the solubility limits [27][28][29] and create alloys with better control over properties through control of composition.…”
Section: Methodsmentioning
confidence: 99%
“…In parallel, observations by electron microscopy revealed In-rich dot-like features in InGaN quantum wells456, which are thought to result from spinodal decomposition. Similarly, for InAlN there exists a large miscibility gap though AlGaN is not expected to decompose278. Spinodal decomposition is a common and technically beneficial process9 for a number of metals and ceramics1011 such as TiAlN.…”
mentioning
confidence: 99%